Islamic Law Analysis of Guidelines for Implementing Contracts in Nuri Savings and Loans and Sharia Financing Cooperatives (KSPPS) East Java - Suhaimi Suhaimi; Abdul Mukit; Naufal El Fany; Moh. Kamil (International Conference on Islamic Economic (ICIE), 2022)
The aim of Sharia Cooperatives is to improve the welfare of members in particular and society in general and to contribute to building a just economic order in accordance with Islamic principles. Strengthening this principle, of course, must start from the contract as sharia legitimacy from the practices carried out by the Cooperative including the Nuri East Java Savings and Loans and Sharia Financing Cooperative (KSPPS). The formulation of the problems posed are 1) How is the Contract Implementation in the KSPPS Nuri East Java Contract Manual; 2) What is the analysis of Islamic law on the implementation of the contract? This research is in the nature of a text study of contract implementation manuals at KSPPS Nuri, East Java, so the method used is a literature survey, namely searching for and studying written materials related to the object of study. The findings of this study are that the contracts practiced at KSPPS Nuri East Java in general do have a strong foundation in Islamic law and are in accordance with the DSN MUI fatwa. Because the foundation of the MUI's DSN fatwa besides ummahatul mashadir such as the Al-Qur'an, hadith, ijma' and qiyas are also the views of the scholars in fiqh books.